Carbon Dioxide capture and storage - Metz, Bert; Loos, Manuela; Davidson, Ogunlade; Coninck, Heleen de; Meyer, Leo; Intergovernmental Panel On Climate Change (Cambridge, United Kingdom Cambridge University Press, 2005)
This Intergovernmental Panel on Climate Change (IPCC) Special Report provides information for policymakers,<U+000d><U+000a>scientists and engineers in the field of climate change and reduction of CO2 emissions. It describes sources,<U+000d><U+000a>capture, transport, and storage of CO2. It also discusses the costs, economic potential, and societal issues of the<U+000d><U+000a>technology, including public perception and regulatory aspects. Storage options evaluated include geological<U+000d><U+000a>storage, ocean storage, and mineral carbonation. Notably, the report places CO2 capture and storage in the context<U+000d><U+000a>of other climate change mitigation options, such as fuel switch, energy efficiency, renewables and nuclear energy.
Monografía electrónica gratuita
Keywords: Dióxido de carbono; Cambios climáticos; Libros electrónicos